Decreased reactive oxygen species concentration in the elongation zone contributes to the reduction in maize leaf growth under salinity - Rodriguez, Andrés Alberto (2004)
Reactive oxygen species (ROS) in the apoplast of cells in the growing zone of grass leaves are required for elongation growth. This work evaluates whether salinity‐induced reductions in leaf elongation are related to altered ROS production. Studies were performed in actively growing segments (SEZ) obtained from leaf three of 14‐d‐old maize (Zea mays L.) seedlings gradually salinized to 150 mM NaCl. Salinity reduced elongation rates and the length of the leaf growth zone. When SEZ obtained from the elongation zone of salinized plants (SEZs) were incubated in 100 mM NaCl, the concentration where growth inhibition was approximately 50%, O2•– production, measured as NBT formazan staining, was lower in these than in similar segments obtained from control plants. The NaCl effect was salt‐specific, and not osmotic, as incubation in 200 mM sorbitol did not reduce formazan staining intensity. SEZs elongation rates were higher in 200 mM sorbitol than in 100 mM NaCl, but the difference could be cancelled by scavenging or inhibiting O2•– production with 10 mM MgCl2 or 200 µM diphenylene iodonium, respectively. The actual ROS believed to stimulate growth is •OH, a product of O2•– metabolism in the apoplast. SEZs elongation in 100 mM NaCl was stimulated by a •OH‐generating medium. Fusicoccin, an ATPase stimulant, and acetate buffer pH 4, could also enhance elongation in these segments, although both failed to increase ROS activity. These results show that decreased ROS production contributes to the salinity‐associated reduction in grass leaf elongation, acting through a mechanism not associated with pH changes.